The Role of Farmers' Groups in Increasing Rice Farming Production - Yanti Sasmita; Fatmah Fatmah; Nurmala Nurmala; Mahdar Mahdar; Sulham Sulham (Agribusiness Journal, 2025)
This study aims to determine the role of farmer groups in the implementation of rice farming activities in Tinigi Village and the relationship between the role of farmer groups in increasing rice farming production in Tinigi Village, Galang District, Tolitoli Regency. The analysis method used is a descriptive analysis method using a Likert Scale and Multiple Linear Regression to determine the influence of learning classes, cooperation facilities and production units. The results of the study show that (1) the role of farmer groups in rice farming is categorized as high, both as a learning class, cooperation facilities and production units (2) The results of the Determination Coefficient Test (R) of multiple linear regression analysis that R is 0.532 or 53.2% means that the percentage of contributions affects learning classes, cooperation facilities and production units. The results of the F Test show that the independent variables simultaneously have a significant effect on the dependent variable. The results of the T Test show that learning classes (X1), cooperation facilities (X2) production units (X3) affect the role of farmer groups, proven by using the T Test.